Peran Tokoh Agama Islam dalam Menguatkan Pendidikan Penanganan Wabah Covid-19 di Desa Wonokromo Bantul Yogyakarta - Silmiah Refi Illahi’ah; Ahmad Shofiyuddin Ichsan; Ali Mustaqim; Heri Kuswanto (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This study aimed to reveal the role of Islamic religious leaders in strengthening education in handling the Covid-19 pandemic in Wonokromo, Pleret Bantul, Yogyakarta. This research was a field research that used descriptive qualitative methods with a case study approach. In this research, the data collection method used passive participatory observation, structured and semi-structured interviews and documentation. The data analysis method used was a circular model and the validity of the data using source triangulation. The research results showed that: (1) The role of religious leaders as role models greatly helped the community in handling the Covid-19 outbreak. The Covid-19 outbreak had had an impact on society in terms of social, psychological and many others. Therefore, the role of religious leaders in this village was as instructors, role models, facilitators, and motivations who provided enlightenment, understanding, and stimuli or advice so that people stayed positive and stayed calm in facing the Covid-19 outbreak. (2) The role impact of Islamic religious leaders in strengthening education in handling the Covid-19 outbreak in this village were: a) maintaining aqidah in the community, b) people feeling safe and aware of health protocols, and c) people being sincere and patient in dealing with plague.